Benzimidazole resistance in Argentinian cattle gastrointestinal nematodes by nemabiome metabarcoding and β-tubulin deep amplicon sequencing - Maté, María Laura (2025)
The convergence of our understanding of the molecular mechanisms underlying anthelmintic resistance with advances in sequencing technologies has enabled the development of molecular approaches for resistance diagnosis. The aim of this study was to evaluate the benzimidazole (BZD) resistance status of gastrointestinal nematode (GIN) species infecting cattle. To achieve this we conducted the first genomic identification and study of BZD resistance status of GIN species infecting cattle across six commercial farms in Buenos Aires, Argentina, using ITS-2 and β-tubulin isotype-1 genes sequencing. Seven GIN species were identified: H. placei (64.1%), C. punctata (26.6%), O. radiatum (3.6%), O. ostertagi (3.5%), H. contortus (1.1%), C. oncophora (0.9%) and T. axei (0.2%). Screening for SNPs identified 4 BZD-resistant polymorphisms: F167Y, E198A, E198L and F200Y. C. punctata, C. oncophora, H. contortus, and O. ostertagi harbored one or more of BZD resistant alleles, whereas H. placei and T. axei have only susceptible alleles. Ostertagia ostertagi population have undergone strong selective pressure as a results of BZD administration. By contrast, C. punctata exhibited high richness in susceptible and resistant alleles both before and after BZD treatment, suggesting that this species has not undergone strong selective pressure. Monitoring the prevalence and geographic distribution of β-tubulin gene polymorphisms associated with BZD resistance is essential for detecting and tracking the emergence and spread of resistance.